Hierarchical secure virtualization model for cloud. - Manavi, Sina; Mohammadalian, Sadra; Udzir, Nur Izura; Abdullah, Azizol (2012)
Cloud services are providing on-demand resources via virtualization technologies. This will make cloud computing a potential target for cyber attacks. Most proposed security models for virtualization are working above virtualization on host OS. Almost all proposed cloud security models suffers from this problem in that these models have very limited control over virtualization. In this paper a Hierarchical Secure Virtualization Model (HSVM) is proposed to provide threat quarantine and conquer in addition to complete control on virtualization. HSVM needs to be implemented under the virtualization level and eventually moving up to the guest OS. This security model has the potential to protect various cloud service models implemented by cloud vendors, such as IaaS, PaaS, dSaaS, and SaaS, and improves cloud vendor control level in IaaS. To the best of our knowledge, there is no similar model or implementation like HSVM, able to protect the cloud from DDoS attack, unauthorized access, data leakage as well.